A study on group involvement and the gender difference in self-actualization - Palacio, Irwin D. (1998)
The study sought to determine whether gender is a factor in the self-actualization of individuals. It also sought to find out whether the number of organizations and the level of organizations are factors in the same process. It is presumed by the study that gender informs the social relations each person maintains, and the social groups we get involved in conversely informs our development and self-actualization. Questionnaires utilizing scale to measure the level of accomplishment in the different levels of Maslow's hierarchy. The results were subjected to cross tabulation and Pearson's correlation to provide the study with its results. The study found that males have a higher level of self-actualization, (M= 14.200). This level has a high positive correlation (Pearson's r of 0.596) but has a very low positive correlation (P=0.112) with the level of involvement in the organizations they cited. Females on the other hand reported the same high level of self-actualization, (M=13.4). There is a high positive correlation (P=0.875) between their self-actualization and the number of organizations they joined in. The study concludes that males may have differing motivations for getting involved in social groupings that have nothing to do with the self-actualization of the person. Females, on the other hand, carry the motivations that lead to their personal development, as evinced by the high positive correlations found.
Research paper (B.A.S.S. Psychology) -- University of the Philippines, Tacloban.
Keywords: Self-actualization.; Social science